Analysis of User-Friendly BST Permanent Shelter Using Kansei Engineering and Administrative Law - Brillian Nur Diansari; Aris Prio Agus Santoso; Fadlan Syariel Ali; Fahar Fauzan (International Journal of Mechanical, Industrial and Control Systems Engineering, 2025)
Urban communities in Surakarta City tend to have high mobility which has an impact on rapid growth.  They need a safe, comfort and efficient transportation system. Surakarta City Transportation Agency presents Batik Solo Trans (BST) to answer these needs. However, the presence of BST is not balanced with user comfort at the BST permanent shelter. The incompatibility of shelter facilities with established standards causes users especially the disabled can’t access independently. This research aims to analyze user assessments and needs using Kansei Engineering and Administrative Law methods to determine the components to create a user-friendly BST permanent shelter. Purposive sampling was used to obtain data from 130 respondents based on interviews, questionnaires and observations. The results showed that comfort and equality are mandatory standards for creating a user-friendly BST permanent shelter. There are 5 aspects that have a significant influence on these standards. Those aspects are clean shelter, clear shelter, strategic location, appropriate shelter width and appropriate of shelter’s access height.